DAMPAK KORUPSI BANSOS TERHADAP KESEJAHTERAAN MASYARAKAT DALAM PANDANGAN MAHASISWA SEKOLAH TINGGI DESAIN INDONESIA - Fitriyyah, Nurfadilah .; Rachman, Rizki Maulana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This article explores the impact of corruption on social assistance programmes and its effect on community welfare from the perspective of design students. Corruption, which is a practice that harms both the state and society, often hinders the effectiveness of social assistance programmes, which should aim to improve social welfare. Design students, with different backgrounds and approaches, produce different perspectives in analysing the impact of corruption on social welfare. Through case studies and qualitative analysis, this article shows how corruption can affect social assistance distribution, service quality, and community satisfaction. The results show that design students have an assessment of social assistance corruption cases and design students can play an important role in reducing corruption and increasing the effectiveness of social assistance, so that it can contribute to improving people's welfare.